Nonmelanoma Skin Cancers: Embryologically Relevant Sites and UV Exposure. Issue 4 (7th April 2020) - Nicoletti, Giovanni; Tresoldi, Marco Mario; Malovini, Alberto; Francesco, Borelli; Faga, Angela
Abstract : Background: Traditionally, nonmelanoma skin cancers (NMSCs) are considered mainly UV-related malignancies. Nevertheless, a strong correlation between the embryologically relevant sites (ERS) of the head and neck and the preferential sites of onset of basal cell carcinomas (BCCs) has long been supposed and demonstrated. The aim of this research was the investigation of the potential correlation between the ERS of the head and neck and the sites of tumor onset in all of the NMSCs. Methods: The distribution of 1165 NMSC was correlated with the ERS of the head and neck using the universally accepted anatomical diagrams featuring the congenital head and neck clefts and an original anatomical diagram showing the most credited sites of the embryonic fusion planes of the auricle. Results: In our sample, both BCC and SSC display an increased likelihood of onset in the ERS of the head and neck. A proportion of 93.10% BCCs was distributed within ERS, while 6.90% derived from non-embryologically relevant sites ( P < 0.001). A proportion of 69.70% SCCs was distributed within ERS, while 30.30% derived from non-embryologically relevant sites ( P < 0.001). The probability of tumors within ERS was significantly higher for BCC versus SCC ( P < 0.001), with BCCs having a 5-fold increase in the probability of occurring in ERS compared to SCCs ( P < 0.001). Conclusions: The ERS might host areas of cellular instability yielding to the development of an NMSC. The environmental UV exposure plays a relatively main role versus dysontogenic factors in the pathogenesis of SCC.